Korelasi Korelasi Digital Religious Literacy dan Kemampuan Critical Thinking Mahasiswa PAI dalam Menangkal Radikalisme di Media Sosial - Muhammad Qusairi; Muhammad Alfi Hidayat; Muhammad Rizqo Qolbiy; Muhamad Sabirin; Yahya Mof (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
Social media has become a double-edged sword; acting as a space for religious learning while simultaneously serving as a medium for spreading radicalism. As digital natives, students are vulnerable to extremist narratives if not equipped with adequate cognitive immunity. This study aims to examine the influence of Digital Religious Literacy and Critical Thinking skills on the resilience of Islamic Religious Education (PAI) students in countering radical narratives. Using a quantitative approach with a correlational method, this study involved 30 PAI students selected through random sampling. Data collection instruments used a Likert scale questionnaire that had been tested for validity and reliability. Data analysis was performed using multiple linear regression. The results showed that: (1) The level of digital religious literacy and counter-radicalism attitudes of students were in the